Deformation modes for the post-critical analysis of thin-walled compressed members by a Koiter semi-analytic approach. (April 2017) - Garcea, Giovanni; Leonetti, Leonardo; Magisano, Domenico; Gonçalves, Rodrigo; Camotim, Dinar
Highlights: A semi-analytic solution for the initial post-critical behavior of compressed thin walled members with generic cross sections is presented. The Koiter approach and the method of separation of variables allow a decoupled sinusoidal series solution along the beam axis. A specialized integration scheme furnish accurate results with a few series terms and a very low cost, with respect to standard finite element analyses. The method is then used to highlight the reason of the poor behavior of beam models enriched with cross section deformation modes in reconstructing the post-critical solution. Successful strategies are proposed in order to overcome these limitations. Abstract: In this paper a semi-analytic solution for the post-critical behavior of compressed thin walled members with generic cross sections is presented. It is based on the Koiter approach and the method of separation of variables. The buckling solution is exactly evaluated using a single sinusoidal function and the initial post-critical behavior is obtained as a decoupled sinusoidal series solution along the beam axis. A specialized integration scheme allows obtaining the solution with only a few terms and a very low cost, with respect to standard finite element analyses. This tool is then used to highlight the reason of the poor behavior of beam models enriched with cross section deformation modes in reconstructing the post-critical solution. Successful strategies are proposed in order to overcome these limitations. A series of numerical tests are reported.